Sustained CD8+ T-cell responses induced after acute parvovirus B19 infection in humans. - Norbeck, O; Isa, A; Pöhlmann, C; Broliden, K; Kasprowicz, V; Bowness, P; Klenerman, P; Tolfvenstam, T (2005)
Murine models have suggested that CD8+ T-cell responses peak early in acute viral infections and are not sustained, but no evidence for humans has been available. To address this, we longitudinally analyzed the CD8+ T-cell response to human parvovirus B19 in acutely infected individuals. We observed striking CD8+ T-cell responses, which were sustained or even increased over many months after the resolution of acute disease, indicating that CD8+ T cells may play a prominent role in the control of parvovirus B19 and other acute viral infections of humans, including potentially those generated by live vaccines.